Metagenomic analysis uncovers novel hepadnaviruses and nackednaviruses - Haijing Ben; Xuejun Wang; Pengxiang Yang; Lin Li; Pengxiang Liu; Yuxue Gao; Yanjun Wang; Yali Liu; Chunyang Huang; Dexi Chen (Scientific Reports)
Abstract The rapid expansion of next-generation sequencing (NGS) databases over the past decade has significantly advanced the identification of novel viruses across a wide range of host species. The Serratus platform and the NCBI Sequence Read Archive (SRA) database were utilized to reassess and analyze publicly available NGS datasets, aiming to identify novel hepadnaviruses and nackednaviruses. Our analysis uncovered multiple complete genomes of previously unrecognized hepadnaviruses and nackednaviruses, including those putatively infecting animals such as hamsters and buffaloes. Additionally, we identified the presence and distribution of various hepadnaviruses and nackednaviruses in African cichlid fishes. In vitro assays employing replication-competent plasmids derived from the identified rice rat and frog hepadnaviruses demonstrated their capacity to support viral replication. The identification of these novel hepadnavirus and nackednavirus species provides valuable insights into the origin and evolutionary history of hepadnaviruses. Moreover, these findings open new avenues for investigating potential animal models to study hepadnavirus replication and infection.